Shadow in the glass : [large type] a Greer Hogan mystery - Hilliard, M. E. (The Greer Hogan mysteries, 2022)
"Murder rocks a wedding celebration at an idyllic lakeside home-and librarian-turned-sleuth Greer Hogan could be next on the killer's guest list in this second exciting installment, perfect for fans of Louise Penny. Librarian Greer Hogan is on hand to celebrate her old friend Sarah Whitaker's nuptials at the Whitaker summer home on beautiful Mirror Lake, just outside the upstate New York village of Lake Placid. But Greer has an ulterior motive-to gather information that could reopen the investigation into her husband's murder, a crime for which she believes an innocent man went to prison. Her plans come to a shuddering halt when a wedding guest goes missing and turns up dead in the lake. The guest, Brittany Miles, was an employee of the Whitaker family whom Sarah had long suspected was up to no good at work. The police have no leads, but Greer-an avid reader of crime fiction who possesses an uncanny knack for deduction-begins her own investigation. She learns that the victim was seen with a mystery man right before she disappeared. Then the autopsy reveals that she didn't drown in the lake after all, but in the reflecting pool in the Whitaker garden. The suspect list is as long as the guest list itself, with no apparent motive. Now, Greer must rely on the wisdom of her favorite fictional detectives to tease out truth from lies-and keep herself out of the killer's sights"--